Blended Learning: Does it help students in understanding mathematical concepts? - Wahyu Setyaningrum (Jurnal Riset Pendidikan Matematika, 2018)
The rapid development of technology offers many advantages to the proses of learning in the classroom. This experimental research aimed to investigates the effectiveness of learning mathematics delivered through blended learning. In particular, this study compared the effectiveness of blended learning using Moodle and traditional one in relation to students’ conceptual understanding. The data was gathered through written test and interview. This study involved 127 students of grade eight secondary school. The data shows that students who learn in blended learning approach have better conceptual understanding rather than their counterparts. The students claim that they can access learning material and revisit some difficult material in their convenience time. Nevertheless, there are some obstacles faced by students related to maintaining their motivation to learn independently and keeping distraction off to access other website when they learn online.Key words: blended learning, conceptual understanding